Flowgraph models for multistate time-to-event data - Huzurbazar Aparna V (Chichester John Wiley, 2005)
This book offers a practical, application-based approach to flowgraph models for time-to-event data. It clearly shows how this innovative new methodology can be used to analyze data from semi-Markov processes without prior knowledge of stochastic process
Keywords: Flowgraphs; Reliability(Engineering)-statistical methods; Stochastic processes